The funding model of small and medium social enterprises in KwaZulu-Natal, South Africa - Remedan Hasseno; Orthodox Tefera; Simon Taylor (The Southern African Journal of Entrepreneurship and Small Business Management, 2024)
Background: Small and medium social enterprises (SMSEs) in developing countries, particularly in South Africa, play a crucial role in a country’s economy. With an entrepreneurial mindset, they respond innovatively to social, economic and environmental societal problems. However, SMSEs in emerging economies experience critical survival and performance challenges, including financial sustainability. Thus, investigating the funding model is important to overcome those challenges.